Single Nucleotide Polymorphism in KIR2DL1 Is Associated With HLA-C Expression in Global Populations - Vargas, Luciana de Brito; Dourado, Renata M.; Amorim, Leonardo M.; Ho, Brenda; Calonga-Solís, Verónica; Issler, Hellen C.; Marin, Wesley M.; Beltrame, Marcia H.; Petzl-Erler, Maria Luiza; Hollenbach, Jill A.; Augusto, Danillo G. (Frontiers in Immunology, 2020)
Regulation of NK cell activity is mediated through killer-cell immunoglobulin-like receptors (KIR) ability to recognize human leukocyte antigen (HLA) class I molecules as ligands. Interaction of KIR and HLA is implicated in viral infections, autoimmunity and reproduction and there is growing evidence of the coevolution of these two independently segregating gene families. By leveraging KIR and HLA-C data from 1000 Genomes consortium we observed that the KIR2DL1 variant rs2304224T is associated with lower expression of HLA-C in individuals carrying the ligand HLA-C2 (p = 0.0059). Using flow cytometry, we demonstrated that this variant is also associated with higher expression of KIR2DL1 on the NK cell surface (p = 0.0002). Next, we applied next generation sequencing to analyze KIR2DL1 sequence variation in 109 Euro and 75 Japanese descendants. Analyzing the extended haplotype homozygosity, we show signals of positive selection for rs4806553G and rs687000G, which are in linkage disequilibrium with rs2304224T. Our results suggest that lower expression of HLA-C2 ligands might be compensated for higher expression of the receptor KIR2DL1 and bring new insights into the coevolution of KIR and HLA.